Second primary malignancies of cancer patients: treatment-related carcinogenesis - G. A. Belitskiy; E. A. Lesovaya; K. I. Kirsanov; M. G. Yakubovskaya (Успехи молекулярной онкологии)
Cytostatic drugs used in chemotherapy cause secondary tumors in some patients cured of the antecedent neoplasm. Thus the incidence of second neoplasia for cancer survivors compared with the general population represents a 4-fold to 6-fold increased risk.The review presents recent data on the mechanisms of malignant transformation of cells by cytostatics, on the characteristics of high- risk groups associated with congenital polymorphisms of xenobiotic metabolizing enzymes and DNA repair systems. Increased risk of drug-related cancer was observed in patients with high activity of P450 isoforms, transforming cytotoxic prodrugs into the active electrophilic metabolites and low level of detoxifying enzymes. All things being equal the risk of therapy related neoplasia is higher in patients with low activity of DNA repair enzymes. It is evaluated the possibility of experimental study of new targeted drugs carcinogenic potential in order to minimize the future risk of secondary malignancies.